Factors Influencing The Usage Of Mobile Commerce In Malaysia - Toh, Tsu Wei (2008)
Mobile commerce is any transaction, involving the transfer of ownership or rights to use goods and services, which is initiated and/or completed by using mobile access to computer-mediated networks with the help of mobile devices.